Módulo de enseñanza de la estadística para el ciclo del segundo nivel académico - Buñay Bravo, Miguel Angel (2001)
Introduction. General. Distributions. Measures of central tendency. Graphic representation of frequency distributions. Frequency curve. Measures of dispersion or variability. Odds. Further reading. Bibliography.